1997
DOI: 10.1002/(sici)1097-0290(19970905)55:5<727::aid-bit3>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and biodegradation of formaldehyde in anaerobic methanogenic culture

Abstract: Formaldehyde is present in several industrial wastewaters including petrochemical wastes. In this study, the toxicity and degradability of formaldehyde in anaerobic systems were investigated. Formaldehyde showed severe toxicity to an acetate enrichment methanogenic culture. As low as 10 mg/L (0.33 mM) of formaldehyde in the reactor completely inhibited acetate utilization. Formaldehyde, however, was degraded while acetate utilization was inhibited. Degradation of formaldehyde (Initial concentration ≤30 mg/L) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 12 publications
2
14
0
3
Order By: Relevance
“…The effects of formaldehyde on methanogenesis reversibility are to some extent reported in literature. Whereas some authors report reversible inhibition (Qu and Bhattacharya, 1997), others observed no recovery of gasification process at all (Gonzalez-Gil et al, 2002). The degree of recovery seems to be related to the concentrations of formaldehyde that microorganisms were exposed to (Vidal et al, 1999) and also the time that follows the inhibition period.…”
Section: Effects Of Formaldehyde and Organic Loading Rates In Ph Devesupporting
confidence: 78%
See 2 more Smart Citations
“…The effects of formaldehyde on methanogenesis reversibility are to some extent reported in literature. Whereas some authors report reversible inhibition (Qu and Bhattacharya, 1997), others observed no recovery of gasification process at all (Gonzalez-Gil et al, 2002). The degree of recovery seems to be related to the concentrations of formaldehyde that microorganisms were exposed to (Vidal et al, 1999) and also the time that follows the inhibition period.…”
Section: Effects Of Formaldehyde and Organic Loading Rates In Ph Devesupporting
confidence: 78%
“…The inhibition caused by formaldehyde in biological treatment systems is widely reported in the literature, however with a broad range of critical concentrations. Qu and Bhattacharya (1997) mentioned that formaldehyde concentrations from 20 to 254 mg L À1 cause 50% reduction of methanogenesis activity, which is in agreement to Lu and Hegeman (1998) that observed 50% of anaerobic gasification inhibition in the presence of 150 mg L À1 of formaldehyde in wood glue wastewater. The influence of formaldehyde concentrations over the methanogenic activity is further discussed in the present work.…”
Section: Cod and Formaldehyde Related Discussion -Phase I (Cycles 1-20)mentioning
confidence: 99%
See 1 more Smart Citation
“…Aquatic organisms, for instance, respond negatively to low concentrations of formaldehyde, which is a frequently found contaminant in hospital wastewater [6]. It was reported that formaldehyde in the range of 10-100 mg/L was toxic to the microbial in wastewater treatment system [7][8][9]. In addition, the presence of organochlorine compounds in high concentrations in hospital effluent has also been reported as toxic to aquatic life [10].…”
Section: Introductionmentioning
confidence: 82%
“…However, degradation rates increased as the initial concentration of formaldehyde as increased. Other studies also concluded that an increase in initial formaldehyde concentrations yield inhibition [26,27].…”
Section: Estimation Of Kinetic Parametersmentioning
confidence: 99%